A Dedicated Neurological Intensive Care Unit Offers Improved Outcomes for Patients With Brain and Spine Injuries. (February 2019) - Jeong, Jin-Heon; Bang, JaeSeung; Jeong, WonJoo; Yum, KyuSun; Chang, JunYoung; Hong, Jeong-Ho; Lee, Kiwon; Han, Moon-Ku
Background: Admission to an intensive care unit (ICU) specialized for brain and spine injury patients is associated with improved outcome. We investigated the effects of the first dedicated, combined neurological and neurosurgical ICU (NeuroICU) in Korea on patient outcomes. Methods: The first dedicated NeuroICU in Korea was established in March 2013. We retrospectively analyzed the clinical data and compared the outcomes between patients admitted to the ICU before and after NeuroICU establishment. The predicted mortality of NeuroICU patients was calculated using their Acute Physiology and Chronic Health Evaluation II scores. Patients' functional outcomes were evaluated using their modified Rankin scale (mRS) scores at 6 months after ICU admission, which were obtained from medical records or telephone interviews. Results: We included 2487 patients, 1572 and 915 of whom were admitted prior to and after NeuroICU establishment, respectively. The demographic characteristics, Glasgow Coma Scale scores, and disease proportions did not differ significantly between the groups. The length of ICU stay and the number of days on ventilation were significantly lower in NeuroICU patients than they were in general ICU patients ( P = .024, P = .001). Intensive care unit mortality was significantly lower in NeuroICU patients (7.3% vs 4.7%, P = .012). The predicted mortality was obtained from 473 NeuroICU patients. The mortality ratio (observed mortality/predicted mortality) was 0.34 (8.9%/26.1%), and 228 (48.1%) patients showed good functional recovery (mRS, 0-2). Conclusion: Our findings suggest that admission to a dedicated NeuroICU significantly improves the neurological outcomes of patients with brain and spine injuries, including their postoperative care, in Korea.